EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF STAD WITH GUIDED DISCOVERY LEARNING PADA MATERI POKOK LINGKARAN DITINJAU DARI ADVERSITY QUOTIENT (AQ) - Suriyah, Puput; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract:Â The aims of thisÂ research were to know: (1) which one is providing better mathematics learning achievement, students taught using cooperative learning of STAD with guided discovery learning, STAD or direct learning, (2) which one is having better mathematics learning achievement, students with Adversity Quotient (AQ) climbers, students with AQ campers or students with AQ quitters, (3) at each learning model, whether there are any mathematics learning achievement difference between students with AQ climbers, students with AQ campers or students with AQ quitters, (4) at each type of Adversity Quotient (AQ), whether there are any mathematics learning achievement difference between students taught using cooperative learning of STAD with guided discovery learning, STAD or direct learning. This research was a quasi experimental research using 3x3 factorial designs. The hypotheses testing used two ways ANOVA with unbalanced cell. This research concludes that: (1) students taught using cooperative learning of STAD with Guided Discovery Learning have better mathematics learning achievement than the students taught using STAD and direct instruction, as well as students who were taught using STAD have better mathematics learning achievement than the group of students taught using direct instruction, (2) students achievement with the climbers type of AQ were better than the students with the campers and quitters type of AQ while the students with the campers type of AQ have better mathematics learning achievement than the students with the quitters type of AQ, (3) in the cooperative learning of STAD with guided discovery learning, there was no difference in learning achievement in each type of AQ, in the STAD, there was no difference in learning achievement in each type of AQ, in the direct instruction, students with climbers type of AQ have better mathematics learning achievement than students with quitters type of AQ, (4) for the students who have climbers type of AQ, there was no difference in learning achievement in each learning models, for the students who have campers type of AQ, STAD with guided discovery learning produced better mathematics achievement than direct instruction, for the students who have quitters type of AQ, STAD with guided discovery learning produced better mathematics achievement than direct instruction.Keywords: STAD With Guided Discovery Learning, Adversity Quotient, Mathematics Learning Achievement